2018
DOI: 10.1038/s41598-018-26059-3
|View full text |Cite
|
Sign up to set email alerts
|

Wild and domesticated Moringa oleifera differ in taste, glucosinolate composition, and antioxidant potential, but not myrosinase activity or protein content

Abstract: Taste drives consumption of foods. The tropical tree Moringa oleifera is grown worldwide as a protein-rich leafy vegetable and for the medicinal value of its phytochemicals, in particular its glucosinolates, which can lead to a pronounced harsh taste. All studies to date have examined only cultivated, domestic variants, meaning that potentially useful variation in wild type plants has been overlooked. We examine whether domesticated and wild type M. oleifera differ in myrosinase or glucosinolate levels, and wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
33
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 48 publications
(42 citation statements)
references
References 59 publications
3
33
0
Order By: Relevance
“…It has recently been shown that putative wild type Moringa oleifera differs markedly in its phytochemistry from domestic Moringa oleifera Fahey et al 2018). The two entities differ markedly in the ways that they are used, with domestic M. oleifera eaten frequently, especially in southern India, and the putative wild type being used chiefly medicinally (Olson 2017;Chodur et al 2018). Most studies of the applied properties of Moringa are carried out on the domestic variant of Moringa oleifera, meaning that the other species are very poorly studied.…”
mentioning
confidence: 99%
“…It has recently been shown that putative wild type Moringa oleifera differs markedly in its phytochemistry from domestic Moringa oleifera Fahey et al 2018). The two entities differ markedly in the ways that they are used, with domestic M. oleifera eaten frequently, especially in southern India, and the putative wild type being used chiefly medicinally (Olson 2017;Chodur et al 2018). Most studies of the applied properties of Moringa are carried out on the domestic variant of Moringa oleifera, meaning that the other species are very poorly studied.…”
mentioning
confidence: 99%
“…With the same HPLC method that we used, and considering the sum of the two main peaks of principal glucosinolates, Chodur at al. [ 32 ] obtained two extremely different glucosinolates values for samples from Kenya (1.16 mg/g) and Mexico (109 mg/g).…”
Section: Discussionmentioning
confidence: 99%
“…Breeding approaches are often employed to obtain crops with low GSL content for food or feed purposes [ 26 , 27 , 28 ], while those with high GSL content remain of interest for non-food applications. Therefore, the choice of species should be carefully considered with regard to the downstream purposes of raw materials.…”
Section: Natural Occurrence Of Glucosinolatesmentioning
confidence: 99%